Convalescent Plasma Therapy for Management of COVID-19: Perspectives and Deployment in the Current Global Pandemic - Samad N; Sodunke TE; Banna HA; Sapkota A; Fatema AN; Iskandar K; Jahan D; Hardcastle TC; Nusrat T; Chowdhury TS; Haque M (Dove Medical Press, 2020)
Nandeeta Samad,1 Temitayo Eniola Sodunke,2 Hasan Al Banna,3 Ashmita Sapkota,4 Aneeka Nawar Fatema,5 Katia Iskandar,6 Dilshad Jahan,7 Timothy Craig Hardcastle,8 Tanzina Nusrat,9 Tajkera Sultana Chowdhury,10 Mainul Haque11 1Department of Public Health, North South University, Dhaka 1229, Bangladesh; 2University of Ilorin, Ilorin, Kwara State, Nigeria; 3Institute of Social Welfare and Research, University of Dhaka, Dhaka 1000, Bangladesh; 4Department of Microbiology, Mahidol University, Ratchathewi, Bangkok 10400, Thailand; 5Department of Microbiology, Prima Asia University, Dhaka 1213, Bangladesh; 6School of Pharmacy, Lebanese University, Beirut, Lebanon; 7Department of Hematology, Asgar Ali Hospital, Dhaka 1204, Bangladesh; 8Department of Surgery, Nelson R Mandela School of Clinical Medicine, University of KwaZulu-Natal, Umbilo, Berea 4001, South Africa; 9Department of Microbiology, Chittagong Medical College, Chattogram 4203, Bangladesh; 10Department of Urology, Shaheed Suhrawardy Medical College Hospital, Dhaka 1207, Bangladesh; 11Unit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kuala Lumpur 57000, MalaysiaCorrespondence: Mainul HaqueUnit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kem Perdana Sungai Besi, Kuala Lumpur 57000, MalaysiaTel +60 109265543Email runurono@gmail.comAbstract: The world is striving against the severe crisis of the COVID-19 pandemic. Healthcare professionals are struggling to treat their patients based on nonspecific therapies. Amidst this uncertainty, convalescent plasma therapy (CPT) has appeared to be an interim adjuvant therapy for severely ill patients of COVID-19 until long-term clinical trial treatment options are available. Considering the transfusion-related hazards, especially lung injuries and microbial transmission, where sensitivity is not ensured, rigorous trials should be conducted to determine this therapy’s efficacy. Moreover, the ratio of recovered cases to plasma donors is not satisfying, which questioning this therapy’s availability and accessibility. Although some countries are making the treatment free, the attributable cost mandates a justification for its suitability and sustainability. Our article aimed to review the published facts and findings of CPT’s effectiveness in lowering the mortality rate of COVID-19. This pandemic showed that healthcare systems worldwide need core reform. A unified global collaboration must align and coordinate to face the current pandemic and enhance world readiness for future outbreaks based on health equity and equality.Keywords: convalescent plasma therapy, safety, risk, availability, accessibility, COVID-19, global pandemic